2010
DOI: 10.1007/s10555-010-9262-z
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell marker olfactomedin 4: critical appraisal of its characteristics and role in tumorigenesis

Abstract: Olfactomedin 4 (OLFM4), a member of the olfactomedin domain-containing proteins, is a glycoprotein with molecular weight of approximately 64 kDa. The protein is a "robust marker" of Lgr5+ stem cells and has been localised to mitochondria, nuclei and cell membranes. The bulk of OLFM4 exists in a polymeric form which is held together by disulfide bonds and carbohydrate interactions. Earlier studies revealed that the protein binds to lectins and cadherins, and facilitates cell-cell adhesion. Recent data demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 138 publications
0
55
1
Order By: Relevance
“…Olfml3 belongs to a family of olfactomedin domain-containing proteins with distinct roles in embryonic patterning, cell-cycle regulation, tumorigenesis, and ability to modulate critical signaling circuits such as Notch or Wnt pathways (21,22). Xenopus ONT1 serves as a scaffold protein that recruits the BMP1/Tolloid proteases to their substrate chordin, a BMP antagonist (19).…”
Section: Introductionmentioning
confidence: 99%
“…Olfml3 belongs to a family of olfactomedin domain-containing proteins with distinct roles in embryonic patterning, cell-cycle regulation, tumorigenesis, and ability to modulate critical signaling circuits such as Notch or Wnt pathways (21,22). Xenopus ONT1 serves as a scaffold protein that recruits the BMP1/Tolloid proteases to their substrate chordin, a BMP antagonist (19).…”
Section: Introductionmentioning
confidence: 99%
“…We have tested the differential expression of several stem cell markers such as LGR5, olfactomedin 4 (OLFM4), achaetescute complex homolog 2 (ASCL2) and B lymphoma Mo-MLV insertion region 1 homolog (BMI-1) (49,50) between CRC patients' tumor tissue and their matched normal mucosa. OLFM4 and LGR5 were overexpressed ≥2-fold in 18/22 (82%), ASCL2 in 13/22 (59%) and BMI-1 in 9/22 (41%) tumors (Figure 2).…”
Section: Identification Of Stem Cell Markers For Ctsc Detectionmentioning
confidence: 99%
“…OLFM4 and LGR5 were overexpressed ≥2-fold in 18/22 (82%), ASCL2 in 13/22 (59%) and BMI-1 in 9/22 (41%) tumors (Figure 2). OLFM4 has previously been identified as a good marker of intestinal stem cells and is involved in regulation of cell adhesion and organization of the cytoskeleton (50,51).…”
Section: Identification Of Stem Cell Markers For Ctsc Detectionmentioning
confidence: 99%
“…The encoded protein product, OLFM4, is a member of the olfactomedin-domain family with intracellular localization mostly in the mitochondria. OLFM4 is characterized by a coiled-coil domain at the N-terminus and a conserved olfactomedin domain of ~250 amino acids at the C-terminus (1). OLFM4 commonly exists in gastrointestinal epithelial cells, prostate and bone marrow (2,3), where it participates in cellular processes, including proliferation, apoptosis, metabolism and differentiation (4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was thought that the OLFM4 expression level has no significant association with common clinical variables (9,10). However, a limited number of studies have reported OLFM4 gene expression in breast cancer patients, and the expression levels of this gene in the peripheral blood of tumor patients remain to be documented (1,10,11,17). To assess the association of OLFM4 gene expression with the development and progression of breast cancer, breast cancer tissue and peripheral blood specimens were selected from patients of different histological grades, and these specimens were used to detect OLFM4 expression in the present study.…”
Section: Introductionmentioning
confidence: 99%